A cross-sectional study of water arsenic exposure and intellectual function in adolescence in Araihazar, Bangladesh. (September 2018) - Wasserman, Gail A.; Liu, Xinhua; Parvez, Faruque; Chen, Yu; Factor-Litvak, Pam; LoIacono, Nancy J.; Levy, Diane; Shahriar, Hasan; Uddin, Mohammed Nasir; Islam, Tariqul; Lomax, Angela; Saxena, Roheeni; et al.
Abstract: Background: Exposure to inorganic arsenic (As) from drinking water is associated with modest deficits in intellectual function in young children; it is unclear whether deficits occur during adolescence, when key brain functions are more fully developed. Objectives: We sought to determine the degree to which As exposure is associated with adolescent intelligence, and the contributory roles of lead, cadmium, manganese and selenium. Methods: We recruited a cross-section of 726 14–16 year olds (mean age = 14.8 years) whose mothers are participants in the Bangladesh Health Effects of Arsenic Longitudinal Study (HEALS), and whose household well water As levels, which varied widely, were well characterized. Using a culturally modified version of the WISC-IV, we examined raw Full Scale scores, and Verbal Comprehension, Perceptual Reasoning, Working Memory and Processing Speed Indices. Blood levels of As (BAs), Mn, Pb, Cd and Se were assessed at the time of the visit, as was creatinine-adjusted urinary As (UAs/Cr). Results: Linear regression analyses revealed that BAs was significantly negatively associated with all WISC-IV scores except for Perceptual Reasoning. With UAs/Cr as the exposure variable, we observed significantly negative associations for all WISC-IV scores. Except for Se, blood levels of other metals, were also associated with lower WISC-IV scores. Controlling for covariates, doubling BAs, or UAs/Cr, was associated with a mean decrement (95% CI) of 3.3 (1.1, 5.5), or 3.0 (1.2, 4.5) points, respectively, in raw Full scale scores with a sample mean of 177.6 (SD = 36.8). Confirmatory analyses using Bayesian Kernel Machine Regression, which identifies important mixture members, supported these findings; the primary contributor of the mixture was BAs, followed by BCd. Conclusions: Our data indicate that the adverse consequences of As exposure on neurodevelopment observed in other cross-sectional studies of younger children are also apparent during adolescence. They also implicate Cd as a neurotoxic element that deserves more attention. Highlights: Arsenic exposure is associated with deficits in intelligence in adolescents. Exposure to a mixture of 5 elements was associated with decreased intelligence. Study findings implicate cadmium as a neurotoxic element that deserves more attention. Arsenic exposure in childhood has an impact on a wide range of intellectual functions.